4-Anilino-pyrimidine, novel aldosterone synthase (CYP11B2) inhibitors bearing pyrimidine structures. Issue 9 (1st May 2017) - Meguro, Masaki; Miyauchi, Satoru; Kanao, Yukiko; Naito, Satoru; Suzuki, Kanae; Inoue, Shinichi; Yamada, Keisuke; Homma, Tsuyoshi; Chiba, Kiyoshi; Nara, Futoshi; Furuzono, Shinji
Graphical abstract: Abstract: 2, 2, 2-Trifluoro-1-{4-[(4-fluorophenyl)amino]pyrimidin-5-yl}-1-[1-(methylsulfonyl)piperidin-4-yl]ethanol1 was identified as a novel potent aldosterone synthase inhibitor. Despite large species differences, compound1 inhibits both human and rodent CYP11B2 in a nano-molar range.